Voltage and frequency instability in large PV systems connected to weak power grid - Zhang, Qianjin; Hu, Qi; Sun, Siwei; Mei, Dikui; Liu, Sucheng; Liu, Xiaodong (Frontiers in Energy Research, 2023)
Weak power grid especially the ultra-weak grid severely impacts photovoltaic (PV) system stability. Unlike traditional power system, PV system consists large amount power electronic equipment. System voltage and frequency control are influenced by coupled nonlinear factors and severely affects power system stability. It is found that the voltage regulation of PV system threatens system frequency stability. This paper investigates the voltage and frequency stability of PV system in weak power grid. The voltage problem caused by grid impedance is firstly analyzed, including inverter output voltage and dc side voltage. Then, methods on improving voltage stability are proposed, such as reactive power compensation. The advantages and disadvantages of different compensation methods are compared and the influence of the methods on the stability of system frequency control is analyzed and solved. The work in this paper gives an insight of voltage and frequency stability problem in large PV system, and provides a reference for the stability analysis and improvement of large scale renewable system. The correctness of the theory is finally verified by simulations and experiments.